Wenlong Xue 4201725 Dissertation - wenlong, Xue (2014)
Shadow banking acts a central role in the formation and evolution process of recent financial crisis, arouses widespread concerns across the world. In recent years, China has participated in its own shadow banking system and growing quickly, such as commercial bank’s financial product portfolios, trust business, securities assets management and private financing, to name a few. In this context, whether China’s shadow banking system will trigger systematic financial risk gradually becoming a subject of debate in economic and financial circles. Currently, the risks inherent in shadow banking are mainly concentrated on transforming of liquidity assets. With a view to obtain a comprehensive understanding of shadow banking system and its liquidity risk, this empirical study examines the determinants of shadow banks’ liquidity, which are measured by bank-specific factors (banks’ profitability ratios and internal liquidity and liabilities ratios) and macroeconomic factors. The liquidity ratio (LR) is used to representative liquidity risk of shadow banks, and 22 Chinese shadow banks have been chosen which operated continuously over the period from 2007 to 2012. This research applies the generalized method of moment (GMM) estimator to address the unobserved heterogeneity and endogeneity issues. The results showing several explanatory variables have statistically significant impact on shadow banks’ liquidity, in terms of logarithm of total asset (Size), return on average total assets (ROAA), debt to equity ratio (DER), equity multiplier (EM), debt to assets ratio (DAR) and current assets turnover (CAT).